Fiber-Shaped Energy Harvesting and Storage Devices - Peng, Huisheng (Springer, 2015)
This comprehensive book covers flexible fiber-shaped devices in the area of energy conversion and storage. The first part of the book introduces recently developed materials, particularly, various nanomaterials and composite materials based on nanostructured carbon such as carbon nanotubes and graphene, metals and polymers for the construction of fiber electrodes. The second part of the book focuses on two typical twisted and coaxial architectures of fiber-shaped devices for energy conversion and storage. The emphasis is placed on dye-sensitized solar cells, polymer solar cells, lithium-ion batteries, electrochemical capacitors and integrated devices. The future development and challenges of these novel and promising fiber-shaped devices are summarized in the final part.